2015
DOI: 10.2215/cjn.09761014
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Chronic Dialysis for the Older Patient

Abstract: Recent research highlights the potential burdens of hemodialysis for older patients with significant comorbidities, for whom there is clinical equipoise regarding the net benefits. With the advent of accountable care and bundled payment, previous incentives to offer hemodialysis to as many patients as possible are being replaced with a disincentive to dialyze high-risk patients. While this may offset the harm of overtreatment for some elderly patients, some voice concerns that the pendulum will swing too far b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…2 8 9 In recent years, these factors have increasingly influenced the healthcare delivery of dialysis to the elderly. For instance, conservative management, that is, the active management of symptoms without resorting to dialysis, has been increasingly adopted for elderly patients who are concerned about the burden of dialysis, [10][11][12] as have assisted and unassisted home-based (as opposed to clinic-based or hospital-based) dialysis therapies. 2 13 14 Such models of care, however, are often developed out of cumulative clinical experience, and the development of systematic approaches has been limited by the inadequate amount of empirical data for: decision-making by older populations, their treatment experiences, the implications of dialysis treatment and treatment modality on quality of life or expectations of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…2 8 9 In recent years, these factors have increasingly influenced the healthcare delivery of dialysis to the elderly. For instance, conservative management, that is, the active management of symptoms without resorting to dialysis, has been increasingly adopted for elderly patients who are concerned about the burden of dialysis, [10][11][12] as have assisted and unassisted home-based (as opposed to clinic-based or hospital-based) dialysis therapies. 2 13 14 Such models of care, however, are often developed out of cumulative clinical experience, and the development of systematic approaches has been limited by the inadequate amount of empirical data for: decision-making by older populations, their treatment experiences, the implications of dialysis treatment and treatment modality on quality of life or expectations of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the harms caused by hemodialysis outweigh its benefits in 75 y and older age group patients [16].…”
Section: Resultsmentioning
confidence: 99%
“…A significant proportion of patients in this report changed their opinion towards conservative care. Reasons for that are not distinctively stated by the respondents but insufficient communication, change of perspectives of patients’ at the end of life, and presumed benefits of prolonging life by dialysis treatment may contribute to this attitude as discussed in different studies [6, 8, 9, 14, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Numbers of dialysis patients have doubled in the last two decades to about 80–90,000 [1] reaching a median age of 69 years in men and 73 years in women [2]. Focusing on the limited survival time and insufficient quality of life on renal replacement therapy (RRT) in some of these individuals, the option of conservative treatment or withholding or stopping dialysis treatment with the consequence of providing palliative care may be considered by many renal professionals [3-9]. …”
Section: Introductionmentioning
confidence: 99%